Analisis Pengaruh Ukuran Perusahaan,Likuiditas, Dan Profitabilitas Terhadap Kebijakan Utang - setianingrum, suci; wibowo, heri (Politeknik Sawunggalih Aji, 2025)
Debt policy is a decision taken by an entity or organization in terms of how debt management will be carried out. This study discusses the effect of company size, liquidity, and profitability on debt policy in coal subsector mining companies listed on the Indonesia Stock Exchange. This research is all coal subsector mining companies listed on the Indonesia Stock Exchange (IDX) in 2020-2022. The population was 27 companies using purposive sampling technique. Based on the purposive sampling technique, a sample size of 23 companies was obtained. The type of data used is secondary data. The data analysis technique used is multiple regression analysis with hypothesis testing, namely the t test and f test. The results showed that: (1) Company size has a positive and significant effect on debt policy of 5,029. (2) Liquidity has a negative and significant effect on debt policy of -8,514. (3) Profitability has a negative and significant effect on debt policy of -5,138. Keywords: Company Size, Liquidity, Profitability, and Debt Policy